Smallholder farmers' constraints to maize growth and yield variability in the northern guinea savannah of Nigeria - Dakagan, J.B. (Bayero University Kano, 2021)
Maize yield has been on the decline on smallholder farms, where the bulk of maize for different uses is produced in the Northern Guinea Savannah of Nigeria. This study analyzed smallholder farmers‘ constraints to maize growth and yield variability in the Northern Guinea Savannah (NGS) of Nigeria for yield optimization. It temporally covers 2017 and 2018 at 4 Weeks After Sowing (WAS) and 8WAS. For Ikara in Kaduna State and Doguwa in Kano State, 30 and 31 farmers respectively were purposively selected for the study. Data collected on the ground included normalized difference vegetative index (NDVI), canopy cover (CC), leaf area index (LAI), Plant Height (PH) and insitu maize yield. Remotely sensed images were acquired using the Unmanned Aerial Vehicle (UAV). Soil samples were taken from each quadrat on smallholder farms and composited into 31 samples in Doguwa and 30 in Ikara. Raw images from the UAV multispectral sensors were processed using Pix4D mapper software and ArcGIS 10.4. Results indicated that LAI and CC were efficient in monitoring and estimating yield, and were positively correlated at R2 value of 0.70 to 0.89 in 2017, and R2 of 0.83 to 0.99 in 2018. In 2017, PH estimated maize yield at 8WAS at R2 value of 0.74 in Doguwa and R2 value of 0.59 in Ikara. In 2018, PH estimated maize yield more in Doguwa at 8WAS with R2 value of 0.40, and estimated maize yield more in Ikara at 8WAS with R2 value of 0.60. In combination with LAI and CC, plant height explained yield variability more at the most critical growth stage (8WAS). The highest qualificationin Ikara (63.3%) was secondary certificate and total income (83.3%) came from farm produce. In Doguwa, late onset of rain (96.3%) caused poor timing and early cessation (70.4%) caused poor yield. Income significant influenced maize yield where amount from sales of other crops was significant (p = 0.00389), total income was significant (p = 0.00536), cash spent on maize farm was significant (p = 0.02849) and amount from maize sales also significantly influenced maize yield (p = 0.04455). Coefficient of variability indicated soil properties were low, and 90% had medium variability. Geostatistics indicated that potential of Hydrogen (pH), Sodium (Na), Phosphous (P), Nitrogen (N), Calcium (Ca), Magnesium (Mg) and Organic Matter (OC) are strong in Doguwa. In Ikara N, K and OC had strong spatial dependence. Smallholder farmers were categorized into three clusters. Cluster 1 farmers applied average of 15.3t/ha of manure and realized average maize yield of 5.41t/ha. Cluster 2 farmers had the highest average yield of 5.92t/ha, and applied average manure of 13t/ha with the highest average NPK of 1.38t/ha and Urea of 1.66t/ha respectively. Cluster 3 smallholder farmers applied an average of 7t/ha of manure on their relatively higher average farm sizes of 0.3 ha. Smallholder farmers in cluster 3 realized lowest average yield of 4.6t/ha. Smallholder farmers should invest in manure application as a means of improving maize yield. Interventions by government at national, state and local levels are necessary to strengthen smallholder farmers‘ capacity in acquiring inputs that significantly improves maize yield.